The Effect Of Rap Music On Verbal Creativity In Youth - Siti Rizki Kartika (Journal Basic Science and Technology, 2020)
Verbal creativity is the ability that is expressed verbally, based on data or information that comes from the many answers to problems, which lie in the quantity, effectiveness, and diversity of answers (Munandar, 1985). Increasing verbal creativity can be done through music that prioritizes verbal techniques. This type of music is rap music. This study aims to determine the effect of rap music on verbal creativity in adolescents. The hypothesis proposed is that there is an effect of rap music on verbal creativity in adolescents. The subjects of this study were students of class X and class XI SMA Negeri 16 Medan as many as 28 people. To obtain the data used Verbal Creativity Test from Munandar. Data analysis used non-parametric statistical test, namely the Mann Whitney Test. The results show (1) There is an effect of rap music on verbal creativity which is indicated by a significant value of .000 < .05 with the median value of the experimental group (Mdn = 4) being higher than the control group (Mdn = -1). (2) The resulting effect is 43.56% and is classified as large. From these results it can be concluded that rap music has an influence on verbal creativity in adolescents.